Address book builder for network monitoring - Paraman, Norlina (2005)
Software development for network monitoring is very important to discover new ways of attacking computer networks. The Network Address Book Builder is the software that is aimed at assisting network administrators in their daily work. PHP and Python were the programming languages used. MYSQL (Standard Query Language) database and Tethereal were used to build software that will be running in FKE campus. It currently runs only on Linux operating system. The methodology to gain output includes a few procedures. The software will capture packets when a user logs into the FKE staff portal to check email. A Python script running as a daemon, analyses the packets to produce output like usernames, MAC (Media Access Protocol) addresses and IP (Internet Protocol) addresses. MAC address and IP address will be matched automatically on the MySQL database table according to the staff username which are in the database. To find the owner of the packets, administrator need to click MAC Address button on the PHP admin graphic user interface (GUI). Besides, the administrator can also search through the MySQL command line.